2021
DOI: 10.1093/texcom/tgab012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Trigeminal Nerve Stimulation on Auditory Event-Related Potentials

Abstract: Trigeminal sensorimotor activity stimulates arousal and cognitive performance, likely through activation of the Locus Coeruleus (LC). In this study we investigated, in normal subjects, the effects of bilateral trigeminal nerve stimulation (TNS) on the LC-dependent P300 wave, elicited by an acoustic oddball paradigm. Pupil size, a proxy of LC activity, and electroencephalographic power changes were also investigated. Before TNS/sham-TNS, pupil size did not correlate with P300 amplitude across subjects. After TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…When multiple statistical tests were performed, a bootstrap procedure was applied as previously described [ 42 ]. As the same size as the original sample ( n = 10), a new population of participants was performed, allowing repetition.…”
Section: Methodsmentioning
confidence: 99%
“…When multiple statistical tests were performed, a bootstrap procedure was applied as previously described [ 42 ]. As the same size as the original sample ( n = 10), a new population of participants was performed, allowing repetition.…”
Section: Methodsmentioning
confidence: 99%
“…This indicated an increased arousal state and correlated with better functional recovery. Under healthy conditions, TNS enhances the signal-to-noise ratio of cortical neurons, allowing subjects to reach optimal discriminative performance in the oddball task at lower levels of neural activation (Tramonti Fantozzi et al 2021 ).…”
Section: Effects Of Trigeminal Nerve Stimulationmentioning
confidence: 99%
“…This approach seems particularly relevant since many ERP components have been operationally related to several specific neurocognitive processes [ 86 , 87 ], including attention, working memory, and decision-making [ 88 , 89 , 90 ]. Both studies used short-term TNS administration but, interestingly, one study [ 91 ] used bilateral transcutaneous stimulation of the trigeminal motor branches (over the masseter belly, incisura sigmoidea), while in the other [ 92 ], the IoN sensitive branch was bilaterally stimulated.…”
Section: How Trigeminal Nerve Stimulation May Affect Cognitive Functionmentioning
confidence: 99%
“…In the first study, Fantozzi and colleagues [ 91 ] showed in 13 healthy subjects a reduction of the amplitude of the P300 wave elicited by an acoustic oddball paradigm in several cortical areas, and a positive correlation between P300 amplitude in frontal and median cortical region and pupil size. The authors ascribed these results to increased cortical norepinephrine (NE) levels due to a TNS-augmented activity of LC neurons.…”
Section: How Trigeminal Nerve Stimulation May Affect Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation